Sintesis Nanopartikel Hematit (α-Fe₂O₃) dari Limbah dengan Variasi Konsentrasi Ekstrak Daun Pepaya (Carica Papaya L) - Nidayanti, Nidayanti; Khoiroh, Llik Miftahul (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2024)
Lathe iron waste contains high iron elements, namely 97.11%, which can potentially be a precursor in hematite synthesis. Hematite is an iron oxide with high stability, high durability, good covering ability, strong coloring power, and non-toxic properties that can be used as a pigment. The method used in this research was precipitation with varying concentrations of papaya leaf extract, namely 20%, 30%, and 40%. The synthesis results were characterized using XRD, Color reader, FTIR, and SEM instruments. This research examines the effect of varying papaya leaf extract concentrations on hematite pigment characteristics. The results of XRD characterization show that the synthesized product is hematite with a rhombohedral structure, which has a crystal size of 32 – 39 nm. Color grades include L*, a*, b*, and C*, produced according to the standard range of hematite pigments. Variations in the concentration of papaya leaf extract show that the greater the concentration of the extract, the darker the red pigment produced. FTIR characterization results show the presence of Fe-O groups at wave numbers 518 and 432 cm-1. The SEM results are aggregate, with average particle sizes for each variation of 2.1, 41.0, and 8.1 nm, respectively.